2003
DOI: 10.1073/pnas.1834399100
|View full text |Cite
|
Sign up to set email alerts
|

Hypogonadotropic hypogonadism due to loss of function of the KiSS1-derived peptide receptor GPR54

Abstract: Hypogonadotropic hypogonadism is defined as a deficiency of the pituitary secretion of follicle-stimulating hormone and luteinizing hormone, which results in the impairment of pubertal maturation and of reproductive function. In the absence of pituitary or hypothalamic anatomical lesions and of anosmia (Kallmann syndrome), hypogonadotropic hypogonadism is referred to as isolated hypogonadotropic hypogonadism (IHH). A limited number of IHH cases are due to loss-of-function mutations of the gonadotropin-releasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
1,446
1
52

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 2,129 publications
(1,525 citation statements)
references
References 36 publications
26
1,446
1
52
Order By: Relevance
“…6,7 Lack of KP signaling via the GPR-54 receptor is associated with reproductive system failure. 8 Cleavage of the KP 45−54 peptide between residues 51 and 52 by matrix metalloproteinases abolishes the activation of GPR-54 by the KP 45−54 peptide. 9 The KP 42−54 and KP 45−54 peptides also activate NPFF receptors, 10,11 and some of the actions of KP peptides could be mediated by NPFF receptor activation.…”
mentioning
confidence: 99%
“…6,7 Lack of KP signaling via the GPR-54 receptor is associated with reproductive system failure. 8 Cleavage of the KP 45−54 peptide between residues 51 and 52 by matrix metalloproteinases abolishes the activation of GPR-54 by the KP 45−54 peptide. 9 The KP 42−54 and KP 45−54 peptides also activate NPFF receptors, 10,11 and some of the actions of KP peptides could be mediated by NPFF receptor activation.…”
mentioning
confidence: 99%
“…Inactivating mutations of two of these, kisspeptin (KP) and neurokinin B (NKB), or their cognate receptors, recently highlighted the crucial role of these neuropeptides in GnRH neurone activation, as these mutations result in a failure to progress through puberty and in adult infertility [6][7][8][9][10][11] . In addition to these major modulators of GnRH secretion, neuropeptide Y, products of the pro-opiomelanocortin protein, gonadotropin-inhibitory-hormone (GnIH) and neurotransmitters such as gamma amino butyric acid and glutamine also regulate GnRH neurone activity 12,13 .…”
Section: B Sex Steroid-dependent Reproductive Diseasesmentioning
confidence: 99%
“…Physico-chemical studies utilising tryptophan fluorescence, conformational memory simulations, nuclear magnetic resonance and ion mobility mass spectrometry have indicated that mammalian GnRH assumes a folded confirmation around Gly 6 . This is depicted in the NMR structure in Figure 3.…”
Section: Gnrh Peptide Agonist and Antagonist Analoguesmentioning
confidence: 99%
See 2 more Smart Citations